Enhancing Rural Science Education through School District-University Partnership - Venicia A. Ferrell; Alexis S. Tharpe (MDPI AG, 2024)
This instrumental case study describes the steps taken to establish and implement a university-school partnership to improve rural science teachers' content knowledge and teaching practices and students' achievement in elementary science and high school biology courses. Our research questions explored the impact of professional development and place-based learning on student outcomes, with the study's methodology involving needs assessments, teacher training, and continuous support through modeling and coaching. The findings include gains in achievement and substantial gains in science education. The findings have implications for the design, implementation, and evaluation of university-school partnerships designed to build teachers' capacity to deliver high-quality science education and improve student success in rural school districts.